Everyone Counts: a citizen's number book - Grodin, Elissa (Chelsea, MI Sleeping Bear Press, 2006)
Helps young readers better understand and appreciate their roles as citizens of our country. Using numbers, this book takes readers on a tour through America's system of government. Starting with the constitution to amendments passed thus far (27), to the number of senators in the Senate (100), the parties, processes, people, and history of our government are explained.
1 - 6
Keywords: Citizenship - United States; United States - Politics and government